Persistence and geochemical differentiation of drilling waste in unconsolidated deep-sea sediments from the Ulleung Basin, East Sea - Jong-Hwa Chun; In Kwon Um; Yong Hoon Kim (Marine Pollution Bulletin, 2026)

Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

Multivariate integration of physicochemical and targeted metabolite profiles with sensory data for the predictive modeling of taste intensities in fermented kimchi - In Min Hwang; Daun Kim; Seul-Gi Jeong; So Yeong Mun; Chang Hee Jeong; Jong-Hee Lee; Ho Myeong Kim (Food Research International, 2026)

Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Position-dependent selenium substitution in conjugated polymers for enhanced doping efficiency and thermoelectric performance - Bomi Kim; Sang Eun Yoon; Daeyeon Lee; Kwangil Jo; Hayoung Park; Seok In Lee; Kyungmin Kim; Min Thein Kyaw; Songhee Oh; Yuchan Heo; Yubhin Cho; Felix Sunjoo Kim; et al. (Chemical Engineering Journal, 2026)

Camellia sinensis (L.) mitigates copper oxide nanoparticles-induced lung inflammation and mucus production through suppressing MAPK signaling and MUC5AC - Woong-Il Kim; Seol Jang; So-Won Pak; Sin-Hyang Park; Ba-Reun Jin; Jong-Choon Kim; Changjong Moon; Joong-Sun Kim; Young-Kwon Cho; Taesoo Kim; In-Sik Shin (Molecular & Cellular Toxicology, 2026)

Establishing a gravity observation system using a superconducting gravimeter: toward future applications - Gracia Kim; In-Mook Choi; Hong Jong Oh; Danbi Hong (Geosciences Journal, 2026)

Bee pollination enhances fruit development and delays ripening by modulating the transition of ethylene biosynthesis and receptor dynamics in tomato (Solanum lycopersicum L.) - Ji Yeong Ham; Yong-Tae Kim; Jong Hwa Shin; Keono Kim; Jeehye Sung; Chuleui Jung; Hataitip Nimitkeatkai; Bongsu Choi; Byung-Chun In (Horticulture, Environment, and Biotechnology, 2026)

Fourier-based periodicity analysis and lightweight RC calibration for heating load modeling under limited sensing - Seon-In Kim; Deuk-Woo Kim; Eui-Jong Kim (Energy and Buildings, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

A 13-week repeated oral toxicity study of Mycoleptodonoides aitchisonii (Agaricomycetes) in Sprague–Dawley rats - In-Hyeon Kim; Sung-Hwan Kim; Joung-Wook Seo; Young-Ju Lee; Han Na Suh; Jong-Choon Kim (Toxicological Research, 2026)

Single-atom Cu-N/O aerogel nanozymes with dual enzymatic activities for point-of-care detection of multiple neurotransmitters - Thinh Viet Dang; Hyun Uk Lee; Ji-In Park; Jong-Seong Bae; Moon Il Kim (Chemical Engineering Journal, 2026)

Genome wide characterization and expression profiling of protein disulfide isomerase (PDI) gene family members in watermelon under cold stress - Nihar Sahu; Uzzal Somaddar; Ga-Eun Bok; Dhanasekar Divya; Ijaz Yaseen; Hoy-Taek Kim; Bo-Kook Jang; Jong-In Park (Genes & Genomics, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Regeneration of Fe(II) EDTA by S(IV) oxyanions and electrochemical reduction: Lowering Fe(II)EDTA-NO/Fe(II) EDTA ratio to maximize DeNOX performance - Beomseo Kim; DongYeon Kim; Jong-In Han (Chemical Engineering Journal, 2026)

Estimation of radiogenic heat production rate of deep subsurface rock mass using natural gamma-ray logs - Yeonguk Jo; Myungsun Kim; Yoonho Song; Tae Jong Lee; In-Hwa Park; Changhyun Lee; Eui-Seob Park (Geosciences Journal, 2026)

Biocontrol potential of beauvericin produced in a submerged culture of Beauveria bassiana 331R against cotton aphid Aphis gossypii - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Hyunbok Song; Seulki Kim; Tae Young Shin; Taek Su Shin; Soo‑Dong Woo; Hae Woong Park (BioControl, 2026)

Study on the hydrodynamic performance of toroidal propellers - Il-Rryong Park; Bu-Gun Paik; So-Won Jung; Je-in Kim; Myeong-Eun Kim; Jong-Woo Ahn; Sang-Hwan Kim (Ocean Engineering, 2026)

Evaluation and application of molecular marker sets for developing PHS-resistant wheat in Korea - Hyeonjin Park; Jin-Kyung Cha; So-Myeong Lee; Youngho Kwon; Woo-Jae Kim; Jong-Hee Lee; In-Jung Lee (Euphytica, 2026)
Pre-harvest sprouting (PHS) is a major constraint on wheat production in Korea, reducing grain quality and end-use value. To accelerate the development of PHS-resistant cultivars with improved agronomic performance, we employed a marker-assisted backcrossing (MABC) approach using molecular markers previously reported in the literature. For foreground selection, 81 molecular markers (74 KASP and 7 gel-based) targeting key genes related to PHS resistance, grain quality, and disease resistance were applied. Genome-wide background selection was conducted with 547 KASP markers to monitor recovery of the recurrent parent genome. Genotyping of 94 wheat accessions revealed distinct genetic clustering among domestic cultivars, introduced germplasm, and 1BL.1RS rye translocation lines, demonstrating the effectiveness of the marker set in capturing genome-wide diversity. Using MABC combined with speed breeding, three elite lines were developed by pyramiding favorable alleles from ‘Joongmo2008’ and ‘Tapdong’. Among them, ‘Milyang55’ exhibited strong PHS resistance (germination rate: 21.1%), desirable agronomic traits, and flour quality comparable to ‘Joongmo2008’. Donor genome proportions ranged from 25.5 to 43.0%, confirming efficient recovery of the recurrent parent genome. These results highlight the utility of integrating pre-selected molecular markers with MABC and speed breeding for the rapid development of elite wheat cultivars with improved PHS resistance and end-use quality.

Evaluation of total nitrogen stocks and burial rates in salt marshes and bare flats of Marine National Parks in South Korea - Inha Kwon; Taewoo Kim; Seo Joon Yoon; Shin Yeong Park; In Ok Lee; Dong-U Kim; Hosang Kim; Cheongjae Lee; Young Eun Kim; Changkeun Lee; Bong-Oh Kwon; Jung Kwan Ahn; et al. (Regional Studies in Marine Science, 2025)

Disturbance of benthic topography and macrofauna community by sand mining in EEZ of the South Sea of Korea - Dong-U Kim; Changkeun Lee; Su In Kim; Seong Woon Jeong; Taeha Kim; Eun Pyo Lim; Soonwoo Lee; Soonyoung Wang; Seong Eun Kim; Jong Seong Khim; Ho Kyung Ha (Regional Studies in Marine Science, 2025)

Integrated VOC and non-VOC profiling for stage-specific quality assessment of kimchi fermentation using LC-MS/MS and GC-IMS - Ji Young Jeong; Min Ji Kim; Hyun-Sung Kim; Jong-Hee Lee; In Min Hwang (Food Chemistry, 2025)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

Collagenase and tyrosinase inhibitory compounds from fish gut bacteria Ruegeria atlantica and Pseudoalteromonas neustonica - Jonghwan Kim; Su Jung Hwang; Gyu Sung Lee; Ju Ryeong Lee; Hye In An; Hong Sik Im; Minji Kim; Sang-Seob Lee; Hyo-Jong Lee; Chung Sub Kim (Phytochemistry Letters, 2025)

Impeller-driven scrubber system for enhanced nitric oxide capture using Fe(II)EDTA - Shin Han; Hyun-Woo Kim; Gwangtaek Lee; Sunghyeon Han; Jong-In Han (Journal of Environmental Chemical Engineering, 2025)

Improving acid-free and selective leaching of lithium from end-of-life LiFePO4 batteries using sodium persulfate: Impact of removing organic matter by thermal treatment in an inert atmosphere - Jong-Won Choi; Mooki Bae; Hyunju Lee; Hong-In Kim; Hyun-Woo Shim; Jinyoung Je; Gigap Han; Junhyun Choi; Hyunjoon Lee; Sookyung Kim (Hydrometallurgy, 2025)

Transcriptomic analysis revealed the adaptations of Latilactobacillus sakei to the cold conditions of kimchi fermentation - Min Ji Kim; Ji Young Jeong; Hyun-Sung Kim; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Research International, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Construction of a bacterial surface display system using split green fluorescent protein (GFP) in Escherichia coli - Hae Won Kim; Jae Jung Kim; Jong-In Won (Biotechnology Letters, 2025)

Calcium-Rich Steel Slag as a Reactive Capping Material: Effects on Hydraulic Conductivity and Nutrient Attenuation in Cohesive Intertidal Sediments - Hee-Eun Woo; Valianto Rojulun Afif; Seongsik Park; Maheshkumar Prakash Patil; Ilwon Jeong; In-Cheol Lee; Jong-Oh Kim; Kyunghoi Kim (Journal of Marine Science and Engineering, 2025)
Fine-grained intertidal sediments are typically characterized by low hydraulic conductivity and high nutrient loads, conditions that hinder biogeochemical recovery and exacerbate eutrophication. This study examined the feasibility of calcium-rich steel slag (SS) as a multifunctional capping material for improving both physical and chemical properties of cohesive sediments. Short-term (24 h) column experiments with two slag dosages (25 g and 50 g) revealed that the higher dosage (SS50) increased sediment hydraulic conductivity by 113.2%, likely through Ca2+-mediated flocculation and enhanced pore connectivity. Phosphate (PO4-P) in pore water decreased by up to 64.1%, and effluent dissolved inorganic nitrogen (DIN) declined by 62.8%, indicating combined effects of Ca-driven precipitation, adsorption, and enhanced flushing. However, SS addition also raised pore water pH (to 11.8) and lowered redox potential, leading to transient phosphate release at the effluent boundary under reducing conditions. Cation analysis confirmed Ca2+ stability and Na+ reduction, suggesting improved sediment structural integrity. The results suggest that steel slag is a promising reactive capping material capable of enhancing permeability and controlling nutrient release in cohesive coastal sediments, yet further investigation into long-term ecological effects and dosage optimization is necessary.

AI-driven multivariate time series forecasting of transmembrane pressure in ultrafiltration: A stationarity-aware approach - Dongju Kim; Jong Pil Yun; Taehan Lee; Daewoong Jung; Hong-In Won (Journal of Water Process Engineering, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Evaluation of Brassica nigra germplasm for the development of pre-breeding resources to improve Brassicaceae - Uzzal Somaddar; Nihar Sahu; Sopheap Mao; Su-Won Kim; Ga-Eun Bok; Jong-In Park (Horticulture, Environment, and Biotechnology, 2025)

Evaluating ripeness in post-harvest stored kiwifruit using VIS-NIR hyperspectral imaging - Jeong-Eun Lee; Min-Jee Kim; Bo-Yeong Lee; Lee Jong Hwan; Ha-Eun Yang; Moon S. Kim; In Geun Hwang; Cheon Soon Jeong; Changyeun Mo (Postharvest Biology and Technology, 2025)

Garlic as a modulator of bacterial dynamics and metabolite profiles in kimchi fermentation - Min Ji Kim; Sera Jung; Hyun-Sung Kim; Ji Young Jeong; In Min Hwang; Woojin Jun; Jong-Hee Lee (Food Bioscience, 2025)

A Dual-Modality nanozyme Exploiting ROS-Responsive oxygen Catalysis for Precision NF-κB pathway Suppression in gouty arthritis - Sathiyamoorthy Padmanaban; Sree Samanvitha Kuppa; Omkar Sangabathula; Amal Babu; Adityanarayan Mohapatra; Sung Sun Kim; Hong Yeol Yang; Aravindkumar Sundaram; Hyung Keun Kim; Jong Keun Seon; In-Kyu Park (Chemical Engineering Journal, 2025)

Systemic toxicity and toxicokinetics study of self-assembled-micelle inhibitory RNA-targeting amphiregulin in cynomolgus monkeys following intravenous injection - Hyeon-Young Kim; Tae-Rim Kim; Sung-Hwan Kim; In-Hyeon Kim; Woong-Il Kim; Jun-Hong Park; Youngho Ko; Sungil Yun; Han-Oh Park; Jong-Choon Kim (Toxicological Research, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Coupling nitric oxide capture with ammonia production using Fe(II)(DMPS)2 in the impeller-based wet nitric oxide absorption process - Hyun-Woo Kim; Kwiyong Kim; Ilgyu Lee; Gwangtaek Lee; Seonjeong Cheon; Jong-In Han (Chemical Engineering Journal, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Modulation of fermentation dynamics in kimchi using Leuconostoc mesenteroides starter - Min Ji Kim; Ji Young Jeong; In Min Hwang; Jong-Hee Lee (Food Bioscience, 2025)

Quantification of growth and physiological characteristics in tolerant and sensitive watermelon lines under cold treatment - Ijaz Yaseen; Sanha Choi; Tariq Mukhtar; Jong-In Park; Hoy-Taek Kim (Horticulture, Environment, and Biotechnology, 2025)
Biochemical and physiological processes serve as key indicators for assessing the adverse effects of biotic and abiotic stressors in plants. Due to the limited and incomplete information on the growth, root morphology, and physiology of watermelon lines under cold stress in Korea, this study aimed to evaluate selected cold-tolerant lines (PI254744, SW20, and SW66) and cold-sensitive lines (PI525233 and SW54). The evaluation was based on root and shoot weight, root and shoot length, root morphology, photosynthetic pigments (chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids), and levels of proline, malondialdehyde (MDA), and soluble sugars in root and leaf samples collected at various time points. Two treatments were conducted: one at 28 °C as a control and one at 10 °C to simulate cold stress. The results revealed a decline in growth variables under cold stress compared to the control across all lines. However, the disintegration of root cellular structures and reduction in growth variables were less severe in the tolerant watermelon lines than in the sensitive ones. Under cold stress, proline, MDA, and soluble sugar levels increased in all watermelon lines relative to the control. Notably, the tolerant lines displayed elevated proline and soluble sugar levels, while the sensitive lines had higher MDA content. Furthermore, photosynthetic pigment levels were generally lower in all lines during cold treatment compared to the control, though the reduction was less pronounced in the tolerant lines than in the sensitive ones. A significant positive correlation was found between the percentage reduction in total chlorophyll content and the percentage reduction in growth variables. The lesser reduction in photosynthetic pigments, combined with higher levels of osmoprotectants (proline and soluble sugars) and lower MDA levels in the tolerant lines during cold stress, may suggest underlying mechanisms that warrant further biochemical and molecular studies to better understand cold resistance.

Influence of temperature on growth and reproduction of keystone species, Crangon hakodatei (Caridea, Crangonidae) in the East Sea of Korea - In Ok Lee; Hyeong-Gi Kim; Junsung Noh; Jong Hun Na; Chul-Woong Oh; Jong Seong Khim (Marine Pollution Bulletin, 2025)

Valorization of coffee residues improve bioelectricity generation and benthic nutrient removal in sediment microbial fuel cells - Nurfarhana Nabila Mohd Noor; Hee-Eun Woo; In-Cheol Lee; Jong-Oh Kim; Kyunghoi Kim (Biomass and Bioenergy, 2025)

In vitro study of silver nanoparticles-induced embryotoxicity using a rat whole embryo culture model - Woong-Il Kim; So-Won Pak; Se-Jin Lee; Sin-Hyang Park; In-Sik Shin; Changjong Moon; Wook-Jun Yu; Sung-Hwan Kim; Jong-Choon Kim (Toxicological Research, 2025)

Transcriptome-Based Prediction of the Toxicity of the Marine Biotoxin Okadaic Acid in Human Vascular Endothelial Cells - Jong Hee Kim; Jeong-In Park; Yewon Kim; Mira Park; Jang Kyun Kim; Young-Seok Han; Youn-Jung Kim (Ocean Science Journal, 2025)

Spatial variations of ascidian diets in a glacial retreated fjord of the West Antarctic Peninsula - Dong-U Kim; In-Young Ahn; Jong-Ku Gal; Sun-Yong Ha; Jong Seong Khim (Marine Environmental Research, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Chitosan-gallic acid conjugate edible coating film for perishable fruits - Cho Rok Lee; Su Jin Lee; Tae In Kim; Kiramage Chathuranga; Jong Soo Lee; Sangsik Kim; Min Hee Kim; Won Ho Park (Food Chemistry, 2025)

Simple synthesis of K/P co-doped graphitic carbon nitride to enhance photocatalytic performance under simulated solar irradiation - Jong-Min Lee; Youn-Jun Lee; Jong Ho Lee; Runfa Tan; Jin-Sil Kim; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Environmental Research, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Molecular marker development for specific amplification of Xanthomonas campestris pv. campestris race 8 causing black rot disease in Brassica crops - Sopheap Mao; Yeo-Hyeon Kim; Nihar Sahu; Su-Won Kim; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of General Plant Pathology, 2025)

Jannaschia ovalis sp. nov., a marine bacterium isolated from a tidal flat sediment in the Republic of Korea - Dae Young Kwon; Sang Hyun Lee; Jong Seong Khim; Xiaoyue Xu; Bogun Kim; In-Geol Choi; Yeonjae Yoo; Jae-Jin Kim (Antonie van Leeuwenhoek, 2025)

Effects of exotic Spartina alterniflora invasion on benthic environments in the Yellow Sea - Jongmin Lee; Junsung Noh; Changkeun Lee; In Ok Lee; Inha Kwon; Bong-Oh Kwon; Moo Joon Lee; Jung-Ho Lee; Jongseong Ryu; Jinhyun Kim; Hojeong Kang; Ho Kyung Ha; et al. (Marine Pollution Bulletin, 2024)

Crystalline carbon antioxidase mimics enhancing innate anti-inflammatory immunity for the treatment of rheumatoid arthritis - Chanhee Choi; DaBin Yim; Hyo Keun Kim; Su-Ji Jeon; In-Jun Hwang; Hongwon Kim; Yoonhee So; Sin Lee; Yejoo Yu; Yujin Choi; Hwankyu Lee; Chul-Su Yang; et al. (Chemical Engineering Journal, 2024)

Changes in limpet diet according to habitat type - Dong-U Kim; Jeongsoo Kim; Hanna Bae; Taewoo Kim; Jongmin Lee; In Ok Lee; Junsung Noh; Jong Seong Khim (Marine Pollution Bulletin, 2024)

Metabolic-methane mitigation by combination of probiotic Escherichia coli strain Nissle 1917 and biochar in rumen fluid in vitro fermentation of dairy cow - Jeongkuk Park; Min-Jin Kwak; Min-Geun Kang; Dae-Yeon Cho; Jong Nam Kim; In-Geol Choi; Younghoon Kim (Journal of Environmental Chemical Engineering, 2024)

Genome wide identification of BBP/BPC transcription factor in tomato and its expression profiling in response to abiotic stress - Antt Htet Wai; Dhanasekar Divya; Jong-In Park; Lae-Hyeon Cho; Dohyeon Kim; Md Mustafizur Rahman; Chang-Kil Kim; Mi-Young Chung (Plant Biotechnology Reports, 2024)

A systematic review and BMD modeling approach to develop an AOP for humidifier disinfectant-induced pulmonary fibrosis and cell death - Donghyun Kim; Yusun Shin; Jong-In Park; Donghyeon Lim; Hyunjoon Choi; Seongwon Choi; Yong-Wook Baek; Jungyun Lim; Younghee Kim; Ha Ryong Kim; Kyu Hyuck Chung; Ok-Nam Bae (Chemosphere, 2024)

Breeding a black soybean line with green cotyledon free from lectin, KTI, P34, lipoxygenase, and stachyose - Sarath Ly; Byeong Eon Park; Sang In Shim; Min Chul Kim; Jin Young Moon; Jong Il Chung (Euphytica, 2024)

Highly visible-light-active sulfur and carbon co-doped TiO2 (SC-TiO2) heterogeneous photocatalysts prepared by underwater discharge plasma - Ha-Rim An; Chaehun Lim; Chung Gi Min; Byoungchul Son; Chang-Yeon Kim; Ji-In Park; Jong Pil Kim; Yesul Jeong; Jiwon Seo; Moonsang Lee; Jihyang Park; Young-Seak Lee; et al. (Chemosphere, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Direct recovery of electro-synthesized ammonia from low-concentration nitric oxide using pulse electrodeposited Cu/C catalyst in a catholyte-free system - Hyun-Woo Kim; Jongmin Jin; Marieandre Kim; Kwiyong Kim; Jong-In Han (Chemical Engineering Journal, 2024)

Utilization of coffee waste as a sustainable feedstock for high-yield lactic acid production through microbial fermentation - Seulbi Kim; Jong-Cheol Kim; Yeong Yeol Kim; Jung Eun Yang; Hee Min Lee; In Min Hwang; Hae Woong Park; Ho Myeong Kim (Science of The Total Environment, 2024)

Production and separation of 2,5-furandicarboxylic acid in gamma-valerolactone solvent system using glucaric acid as raw material derived from oxidation of enzymatic hydrolysate of Miscanthus sacchariflorus - Jonghwa Kim; Jong-Chan Kim; Young-Min Cho; Chae-Hwi Yoon; Hyo Won Kwak; June-Ho Choi; Hoyong Kim; In-Gyu Choi (Biomass and Bioenergy, 2024)

Probiotic, Paraprobiotic, and Hydrolyzed Yeast Mixture Supplementation Has Comparable Effects to Zinc Oxide in Improving Growth Performance and Ameliorating Post-weaning Diarrhea in Weaned Piglets - De Xin Dang; Si Yeong Choi; Young Jae Choi; Jong Hwa Lee; Mathieu Castex; Eric Chevaux; David Saornil; Fernando Bravo de Laguna; Guillermo Jimenez; In Ho Kim (Probiotics and Antimicrobial Proteins, 2024)

Correction to: Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Submarine landslides on the Eastern South Korea Plateau (ESKP)—Do pumice-rich tephra layers control slope stability? - Deniz Cukur; In-Kwon Um; David M. Buchs; Seong-Pil Kim; Gee-Soo Kong; Jong-Hwa Chun; Senay Horozal; Seok-Hwi Hong; Shin Yu; Tae-Yeon Kim (Marine Geology, 2024)

Particulate matter-mediated oxidative stress induces airway inflammation and pulmonary dysfunction through TXNIP/NF-κB and modulation of the SIRT1-mediated p53 and TGF-β/Smad3 pathways in mice - Ji-Hye Ha; Ba-Wool Lee; Da-Hye Yi; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Hyeon-Young Kim; Sung-Hwan Kim; In-Sik Shin; Jong-Choon Kim; In-Chul Lee (Food and Chemical Toxicology, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Diesel particulate matter aggravates cyclophosphamide-induced testicular toxicity in mice via elevating oxidative damage - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; Yea-Gin Yang; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2024)

Characterization and distribution of black rot disease causing pathogen-Xanthomonas campestris pv. campestris races of the Jeju Island, South Korea - Jeong-Eui Hong; Hee-Jin Kim; Mohammad Rashed Hossain; Mehede Hassan Rubel; Nihar Sahu; Sopheap Mao; Jong-Goo Kang; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of Plant Pathology, 2023)

Electrochemically-mediated reactive separation of nitric oxide into nitrate using iron chelate - SeokHwan Jeon; Mintaek Im; Kwiyong Kim; DongYeon Kim; Jong-In Han (Chemosphere, 2023)

Field experiments on chemical and biological changes of thin-layer oyster shells capping sediments in dense aquaculture area - Hee-Eun Woo; Ilwon Jeong; Jong-Oh Kim; Young-Ryun Kim; In-Cheol Lee; Kyunghoi Kim (Environmental Research, 2023)

Electron donor–acceptor type delayed fluorescence emitters with inverted singlet and triplet excited states - Youngnam Lee; Jiyun Kim; Soohyeon Lee; Eunji Sim; Jong-In Hong (Chemical Engineering Journal, 2023)

Design strategy of cathodic electrocatalysts to effectively suppress inorganic fouling for long-term stability of reverse electrodialysis - Eunjin Jwa; Hanki Kim; Joo-Youn Nam; Jong-In Han; Namjo Jeong (Chemical Engineering Journal, 2023)

Dual facet passivation of silver halometallate for eco-friendly silver bismuth sulfide near IR photodetector - Ashish Sharma; Hanjae Kim; Gunhee Kim; Jinhyeon Kang; Cheong Beom Lee; Sung Yong Bae; Hochan Song; Kyeounghak Kim; Jong Hyun Kim; In Hwan Jung; Dong-Won Kang; Jihoon Lee; et al. (Chemical Engineering Journal, 2023)

Effects of melamine and cyanuric acid on placental and fetal development in rats - Woong-Il Kim; So-Won Pak; Se-Jin Lee; Changjong Moon; In-Sik Shin; In-Chul Lee; Jong-Choon Kim (Food and Chemical Toxicology, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Study of Overtopping Flow Velocity and Overtopping Layer Thickness on Composite Breakwater under Regular Wave - Made Narayana Adibhusana; Jong-In Lee; Young-Taek Kim; Yonguk Ryu (Journal of Marine Science and Engineering, 2023)
Overtopping flow velocity (OFV) and overtopping layer thickness (OTL) are essential parameters in breakwater design. Several empirical equations to predict these parameters are available in many works of literature, but most of the equations were derived based on impermeable structures such as sea dikes. In this study, we experimented with overtopping waves over a composite breakwater with tetrapod armor units. In the experiments, wave overtopping was generated from regular waves. We used a digital image-based velocimetry method, bubble image velocimetry (BIV), to measure the OFV and digitize the corresponding image to obtain the OLT. The patterns of OFV and OTL with respect to time steps, wave conditions, and corresponding events were provided and discussed. The application of the widely used empirical equations for sea dike to breakwater was also tested by calibrating the coefficients. New empirical coefficients and roughness factors were suggested to reduce the difference between predicted and measured OFV and OLT on breakwater through the bootstrap resampling technique. This study provides modified empirical equations on wave overtopping, which is further applicable to breakwater design.

Food web dynamics in the mangrove ecosystem of the Pearl River Estuary surrounded by megacities - In Ok Lee; Junsung Noh; Beomgi Kim; Inha Kwon; Hosang Kim; Bong-Oh Kwon; Yisheng Peng; Zhan Hu; Jong Seong Khim (Marine Pollution Bulletin, 2023)

Construction of an underwater plasma and Fenton hybrid system for the rapid oxidation of organic dyes and antibiotics - Soo Hyeon Kim; Jiwon Seo; Yongcheol Hong; Yongwook Shin; Hea-Jong Chung; Ha-Rim An; ChangYeon Kim; Ji-In Park; Hyun Uk Lee (Journal of Water Process Engineering, 2023)

Toll-like receptor 4 is a key regulator of asthma exacerbation caused by aluminum oxide nanoparticles via regulation of NF-κB phosphorylation - Je-Oh Lim; Woong-Il Kim; So-Won Pak; Se-Jin Lee; Sung-Hyeuk Park; In-Sik Shin; Jong-Choon Kim (Journal of Hazardous Materials, 2023)

Glucosinolates and Biotic Stress Tolerance in Brassicaceae with Emphasis on Cabbage: A Review - Md. Abuyusuf; Mehede Hassan Rubel; Hoy-Taek Kim; Hee-Jeong Jung; Ill-Sup Nou; Jong-In Park (Biochemical Genetics, 2023)

Natural Variations in the Benthic Environment and Bacterial Communities of Coastal Sediments around Aquaculture Farms in South Korea - Maheshkumar Prakash Patil; Ilwon Jeong; Hee-Eun Woo; Jong-Oh Kim; Dae In Lee; Kyunghoi Kim (Indian Journal of Microbiology, 2023)

A Study on Grid-Cell-Type Maritime Traffic Distribution Analysis Based on AIS Data for Establishing a Coastal Maritime Transportation Network - Hyun-Suk Kim; Eunkyu Lee; Eui-Jong Lee; Jin-Won Hyun; In-Young Gong; Kyungsup Kim; Yun-Sok Lee (Journal of Marine Science and Engineering, 2023)
Recently, marine development plans such as offshore wind farms and marina port facilities have been established to use Korean coastal waters, and research on the development of operational ships such as autonomous ships and water-surface flying ships is being rapidly promoted. Since the marine traffic in Korean coastal waters is expected to increase, the government intends to construct a coastal maritime transportation network that connects Korean coastal waters to guarantee safe ship navigation. Therefore, this study used automatic-identification-system data analysis to obtain quantitative evaluation results on maritime traffic distribution characteristics and utilization levels for the entire Korean coastal waters in grid cell for greater consistency and compatibility. The characteristics of marine traffic distribution at a certain site in coastal Korean waters can be quantitatively examined using the findings of this study, and they may be used as grid-cell-type data-based information. Moreover, the vessel traffic index allows for extensive research while quickly understanding the present level of use of the passing ships by the sea area. In this regard, the findings of this study are expected to be useful for the future development of maritime transportation networks in Korean coastal waters.

Exposure to China dust exacerbates testicular toxicity induced by cyclophosphamide in mice - Woong-Il Kim; Je-Oh Lim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Changjong Moon; Jeong-Doo Heo; Jong-Choon Kim (Toxicological Research, 2023)

3-Hydroxymorphinan protects against hypoxia-induced cell death in primary astrocyte by regulating Ca2+ influx and the glutamate homeostasis - Ok-Hyeon Kim; Gyeong Yun Lee; Kyung Yong Kim; Jong In Son; Tae Woo Jung; Ji Hoon Jeong; Joon Seok Bang; Hyoung-Chun Kim; Yoon Hee Chung; Hyun Jung Lee (Molecular & Cellular Toxicology, 2023)

Significant relationship between Arctic warming and East Asia hot summers - Da‐Seul Kim; Sang‐Yoon Jun; Myong‐In Lee; Jong‐Seong Kug (International Journal of Climatology, 2022)
Arctic warming is of growing interest because it could affect midlatitude climates. Even though numerous studies have paid attention to the relationship between Arctic warming and the midlatitude climate in winter, the influence of Arctic warming on the summer conditions has not been examined in depth. Here we identify a significant relationship between East Asia hot summers and Arctic warming over the Barents and Kara seas. To represent Arctic warming, we define a combined index by simply differencing the normalized surface air temperature and sea‐ice indices. We found that the combined index in July has significantly high correlations with the temperatures in China, Korea, and Japan. While the teleconnection mechanism is not completely revealed, it is evident that warming over the Barents and Kara seas is accompanied by the local development of an anomalous anticyclone and downstream wave trains, which yield a strong anticyclonic circulation over East Asia and the North Pacific. The anticyclonic circulation persists and intensifies until August, which leads to hot summer conditions in East Asia with warm advection and enhanced shortwave radiation. Our results suggest that Arctic climate conditions can be used as a useful precursor of East Asia temperature variations even in summer.

Asian-specific 3’UTR variant in CDKN2B associated with risk of pituitary adenoma - Byeong Ju Youn; Hyun Sub Cheong; Suhg Namgoong; Lyoung Hyo Kim; In Ki Baek; Jeong-Hyun Kim; Seon-Jin Yoon; Eui Hyun Kim; Se Hoon Kim; Jong Hee Chang; Sun Ho Kim; Hyoung Doo Shin (Molecular Biology Reports, 2022)

Evaluation of genotoxicity of SUNACTIVE Zn-P240 in vitro and in vivo - Jeong-Hyun Lim; Jong-Yun Lee; Woong-Il Kim; So-Won Pak; Se-Jin Lee; In-Sik Shin; Jong-Choon Kim (Toxicological Research, 2022)

Performance evaluation of a visual guidance patient-controlled respiratory gating system for respiratory-gated magnetic-resonance image-guided radiation therapy - Hyung Jin Choun; Jung-in Kim; Chang Heon Choi; Seongmoon Jung; Hyeongmin Jin; Hong-Gyun Wu; Eui Kyu Chie; Jong Min Park (Physical and Engineering Sciences in Medicine, 2022)

Subchronic Toxicity Evaluation of Aluminum Oxide Nanoparticles in Rats Following 28-Day Repeated Oral Administration - Sung-Hyeuk Park; Je-Oh Lim; Woong-Il Kim; So-Won Park; Se-Jin Lee; In-Sik Shin; Changjong Moon; Je-Hein Kim; Jeong-Doo Heo; Jong-Choon Kim (Biological Trace Element Research, 2022)

Essential oil from Chrysanthemum boreale flowers modulates SNARE protein-linked mast cell response and skin barrier proteins and ameliorates atopic dermatitis-like lesions in mice - Do Yoon Kim; Kyung-Jong Won; Dae Il Hwang; Su Yeon Lee; In-Ho Choi; Bokyung Kim; Hwan Myung Lee (Horticulture, Environment, and Biotechnology, 2022)

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Comparison of treatment plans between static jaw and jaw tracking techniques in postmastectomy intensity-modulated radiation therapy - Seongmoon Jung; Jung-in Kim; Jong Min Park; Kyung Hwan Shin; Jin Ho Kim; Chang Heon Choi (Physical and Engineering Sciences in Medicine, 2022)

Comparative toxicity of polyhexamethylene guanidine phosphate in three strains of rats - Jong-Hwan Woo; Ki Cheon Kim; Hyeon-Young Kim; In-Hyeon Kim; Sung-Hwan Kim; Kyuhong Lee (Molecular & Cellular Toxicology, 2022)

Protective effect of berberine chloride against cisplatin-induced ototoxicity - Jong-Heun Kim; Jeong-In Baek; In-Kyu Lee; Un-Kyung Kim; Ye-Ri Kim; Kyu-Yup Lee (Genes & Genomics, 2022)
Background Cisplatin (CP) is an effective anticancer drug broadly used for various types of cancers, but it has shown ototoxicity that results from oxidative stress. Berberine has been reported for its anti-oxidative stress suggesting its therapeutic potential for many diseases such as colitis, diabetes, and vascular dementia. Objective Organ of Corti of postnatal day 3 mouse cochlear explants were used to compare hair cells after the treatment with cisplatin alone or with berberine chloride (BC) followed by CP. Methods We investigated the potential of the anti-oxidative effect of BC against the cisplatin-induced ototoxicity. We observed a reduced aberrant bundle of stereocilia in hair cells in CP with BC pre-treated group. Caspase-3 immunofluorescence and TUNEL assay supported the hypothesis that BC attenuates the apoptotic signals induced by CP. Reactive oxygen species level in the mitochondria were investigated by MitoSOX Red staining and the mitochondrial membrane potentials were compared by JC-1 assay. Results BC decreased ROS generation with preserved mitochondrial membrane potentials in mitochondria as well as reduced DNA fragmentation in hair cells. In summary, our data indicate that BC might act as antioxidant against CP by reducing the stress in mitochondria resulting in cell survival. Conclusion Our result suggests the therapeutic potential of BC for prevention of the detrimental effect of CP-induced ototoxicity.

Dose calculation of 3D printing lead shield covered by biocompatible silicone for electron beam therapy - Ohyun Kwon; Hyeongmin Jin; Jaeman Son; Chang Heon Choi; Jong Min Park; Jung-in Kim; Seongmoon Jung (Physical and Engineering Sciences in Medicine, 2021)

In silico analysis and expression profiling revealed Rlm1′ blackleg disease-resistant genes in Chromosome 6 of Brassica oleracea - Arif Hasan Khan Robin; Gopal Saha; Jong-In Park; Rawnak Laila; Md Abdur Rahim; Mita Bagchi; Hoy-Taek Kim; Hee-Jeong Jung; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2021)

Changes in the chemical properties of coir dust with increasing aging time and development of a method for determining moderate aging degree - Yun Seob Kim; In Sook Park; Eunsoo Park; Byoung-Kwan Cho; Chiwon W. Lee; Jong Myung Choi (Horticulture, Environment, and Biotechnology, 2021)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

First report of tomato spotted wilt virus infecting Cirsium setidens in Korea - Seongmu Mun; Su-Yeon Hwang; Na-Kyeong Kim; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

Identification and characterization of carotenoid biosynthesis related genes in a novel dark skinned citrus mutant cultivar ‘Suneat’ - Md. Abdur Rahim; Khandker Shazia Afrin; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2021)

In silico characterization and expression of disease-resistance-related genes within the collinear region of Brassica napus blackleg resistant locus LepR1′ in B. oleracea - Mostari Jahan Ferdous; Mohammad Rashed Hossain; Jong-In Park; Hoy-Taek Kim; Arif Hasan Khan Robin; Sathishkumar Natarajan; Manosh Kumar Biswas; Hee-Jeong Jung; Ill-Sup Nou (Journal of General Plant Pathology, 2020)

In-silico identification and differential expression of putative disease resistance-related genes within the collinear region of Brassica napus blackleg resistance locus LepR2’ in Brassica oleracea - Mohammad Rashed Hossain; Mostari Jahan Ferdous; Jong-In Park; Arif Hasan Khan Robin; Sathishkumar Natarajan; Hee-Jeong Jung; Hoy-Taek Kim; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)
Blackleg disease, caused by Leptosphaeria maculans, greatly affects the production of cabbage ( Brassica oleracea ). However, definitive R-gene(s) are yet to be identified in this crop. In contrast, a number of R-loci have been identified in A- or B-genome crops. Identification of few resistant cabbage genotypes indicates the presence of R-genes in this C-genome crop. High ancestral synteny between Brassica genomes suggests that the collinear regions of known A- or B-genome R-loci may also contain functional R-genes in the C-genome. Strong resistance was observed in the cotyledons of cabbage inbred line SCNU-98 against two L. maculans isolates, 03–02 s and 00–100 s. We investigated the collinear region of the Brassica napus blackleg resistance locus LepR2’ in B. oleracea since both isolates of L. maculans contain corresponding avirulence genes. The locus was collinear to a 5.8 Mbp genomic segment of B. oleracea chromosome C09 containing 13 genes that have putative disease resistance-related domains. High expression of genes Bo9g117290 and Bo9g111510 against isolate 00–100 s, and high expression of genes Bo9g126150 and Bo9g111490 against both isolates in the resistant-line SCNU-98 indicate their putative roles in blackleg resistance, which remained to be functionally verified. This work enhances our understanding of R-gene-mediated resistance to blackleg in cabbage.

Pulmonary inflammation caused by silica dioxide nanoparticles in mice via TXNIP/NLRP3 signaling pathway - Je-Oh Lim; Je-Won Ko; Tae-Yang Jung; Woong-Il Kim; So-Won Pak; In-Sik Shin; Won-Kee Yun; Hyoung-Chin Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

Development of powdery mildew race 5-specific SNP markers in Cucumis melo L. using whole-genome resequencing - Jewel Howlader; Yeji Hong; Sathishkumar Natarajan; Kanij Rukshana Sumi; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Changes in soil properties for 6 years of using the freshwater snail (Ampullaria tischbeini Dohrn) in a reclaimed sodic soil - Jong-Song Jo; Song-Ho Pak; Chol-Ho Ri; Song-Ok Cha; Gwang-Rim Kim; Chon-Il Ri; In-Song Kim (Journal of Soils and Sediments, 2020)

Molecular characterization of Acidovorax citrulli strain NIHHS15-280 causing bacterial fruit blotch disease in Korea and screening of resistance sources in melon - Md. Rafiqul Islam; Mohammad Rashed Hossain; Hoy-Taek Kim; Ujjal Kumar Nath; Md. Abuyusuf; Hee-Jeong Jung; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Effects of Immunostimulants, Prebiotics, Probiotics, Synbiotics, and Potentially Immunoreactive Feed Additives on Olive Flounder ( Paralichthys olivaceus ): A Review - Md Tawheed Hasan; Won Je Jang; Jong Min Lee; Bong-Joo Lee; Sang Woo Hur; Sang Gu Lim; Kang Woong Kim; Hyon-Sob Han; In-Soo Kong (Reviews in Fisheries Science & Aquaculture, 2019)

Molecular Identification and Expression Analysis of Carbonic Anhydrase VII in Pufferfish (Takifugu rubripes) - Kanij Rukshana Sumi; Soo Cheol Kim; Jewel Howlader; Md Rajib Sharker; Kap Seong Choi; Sang Ki Choi; Jong-In Park; Ill-Sup Nou; Kang Hee Kho (Ocean Science Journal, 2019)

Comparison of saline vs. blood replenishment after blood sampling in a rat pharmacokinetic study - Sang-Bum Kim; Kyu-Sang Kim; Heon-Min Ryu; In-Soo Yoon; Hyun-Jong Cho; Suk-Jae Chung; Saeho Chong; Dae-Duk Kim (Journal of Pharmaceutical Investigation, 2019)

Development of a marker for detection of Xanthomonas campestris pv. campestris races 1 and 2 in Brassica oleracea - Mehede Hassan Rubel; Sathishkumar Natarajan; Ujjal Kumar Nath; Michael Immanuel Jesse Denison; Jung Hee-Jeong; Kim Hoy-Taek; Park Jong-In; Nou Ill-Sup (Horticulture, Environment, and Biotechnology, 2019)

Cisplatin-induced ototoxicity involves interaction of PRMT3 and cannabinoid system - Je-Oh Lim; Je-Won Ko; Na-Rae Shin; Tae-Yang Jung; Changjong Moon; Hyoung-Chin Kim; In-Sik Shin; Jong-Choon Kim (Archives of Toxicology, 2019)

Effects of degree and symmetricity of bilateral spectral smearing, carrier frequency, and subject sex on amplitude of evoked auditory steady-state response signal - Jong Ho Hwang; Kyoung Won Nam; Dong Pyo Jang; In Young Kim (Cognitive Neurodynamics, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Intronic Sequence Variations in a Gene with Peroxidase Domain Alter Bolting Time in Cabbage (Brassica oleracea var. capitata) - Md. Abuyusuf; Ujjal Kumar Nath; Hoy-Taek Kim; Manosh Kumar Biswas; Jong-In Park; Ill-Sup Nou (Plant Molecular Biology Reporter, 2018)

Simultaneous analysis and exposure assessment of migrated bisphenol analogues, phenol, and p-tert -butylphenol from food contact materials - Joungboon Hwang; In-Ae Bae; Chanyong Lee; Subi Lee; Jae Chun Choi; Se-Jong Park; Jin-Hwan Hong; Gaeho Lee; MeeKyung Kim (Food Additives & Contaminants: Part A, 2018)

Perfluorinated compounds in food simulants after migration from fluorocarbon resin-coated frying pans, baking utensils, and non-stick baking papers on the Korean market - Heeju Choi; In-Ae Bae; Jae Chun Choi; Se-Jong Park; MeeKyung Kim (Food Additives & Contaminants Part B-Surveillance, 2018)

Identification of NBS-encoding genes linked to black rot resistance in cabbage (Brassica oleracea var. capitata) - Khandker Shazia Afrin; Md Abdur Rahim; Jong-In Park; Sathishkumar Natarajan; Hoy-Taek Kim; Ill-Sup Nou (Molecular Biology Reports, 2018)

Complete Genome Sequence of Bacillus sp. SJ-10 (KCCM 90078) Producing 400-kDa Poly-γ-glutamic Acid - Won Je Jang; Jong Min Lee; Yu-Ri Kim; Md Tawheed Hasan; In-Soo Kong (Current Microbiology, 2018)

A multi-factor approach for process-based seabed characterization: example from the northeastern continental margin of the Korean peninsula (East Sea) - Deniz Cukur; In-Kwon Um; Jong-Hwa Chun; So-Ra Kim; Gwang-Soo Lee; Yuri Kim; Gee-Soo Kong; Senay Horozal; Seong-Pil Kim (Geo-Marine Letters, 2018)

Expression of anthocyanin biosynthesis-related genes reflects the peel color in purple tomato - Song-I Kang; Md Abdur Rahim; Khandker Shazia Afrin; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2018)

Gender affects prognosis of methicillin-resistant Staphylococcus aureus bacteremia differently depending on the severity of underlying disease - Chang Kyung Kang; Yee Gyung Kwak; Youngmi Park; Kyoung-Ho Song; Eu Suk Kim; Sook-In Jung; Kyung-Hwa Park; Wan Beom Park; Nam Joong Kim; Young Keun Kim; Hee-Chang Jang; Shinwon Lee; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Total and Methyl Mercury Concentrations in Antarctic Toothfish (Dissostichus mawsoni): Health Risk Assessment - Minchul Yoon; Mi Ra Jo; Poong Ho Kim; Woo Seok Choi; Sang In Kang; Seok Gwan Choi; Jong Hee Lee; Hee Chung Lee; Kwang Tae Son; Jong Soo Mok (Bulletin of Environmental Contamination and Toxicology, 2018)

Seismicity of the 2016 ML 5.8 Gyeongju earthquake and aftershocks in South Korea - Jimin Lee; Yonggyu Ryoo; Sun Cheon Park; Young Mo Ham; Jong Soo Park; Myeong Su Kim; Sang Mi Park; Hyen Geom Cho; Keun Su Lee; In Sun Kim; Hye Su Kim; Sunhee Bae (Geosciences Journal, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Multi-resolution Hybrid Data Assimilation Core on a Cubed-sphere Grid (HybDA) - Hyo-Jong Song; Ji-Hyun Ha; In-Hyuk Kwon; Junghan Kim; Jihye Kwun (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Intercomparison of Terrestrial Carbon Fluxes and Carbon Use Efficiency Simulated by CMIP5 Earth System Models - Dongmin Kim; Myong-In Lee; Su-Jong Jeong; Jungho Im; Dong Hyun Cha; Sanggyun Lee (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Expression Profiling of the CSDP Transcription Factor Gene Family Points to Roles in Organ Development and Abiotic Stress Response in Tomato (Solanum lycopersicum L.) - Khadiza Khatun; Ujjal Kumar Nath; Jong-In Park; Chang Kil Kim; Ill Sup Nou; Mi-Young Chung (Plant Molecular Biology Reporter, 2018)

Dendropanax morbifera Léveille extract ameliorates cesium-induced inflammation in the kidney and decreases antioxidant enzyme levels in the hippocampus - Hyo Young Jung; Hyun Jung Kwon; Kyu Ri Hahn; Dae Young Yoo; Woosuk Kim; Jong Whi Kim; Yong Jae Kim; Yeo Sung Yoon; Dae Won Kim; In Koo Hwang (Molecular & Cellular Toxicology, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Enhancement and characterization of natural pigments produced by Monascus spp. using Saccharina japonica as fermentation substrate - Sharmin Suraiya; Mahbubul Pratik Siddique; Jong-Min Lee; Eun-Young Kim; Jin-Man Kim; In-Soo Kong (Journal of Applied Phycology, 2018)

A comparative study of Mentha arvensis L. and Mentha haplocalyx Briq. by HPLC - Bing Tian Zhao; Tae In Kim; Young Ho Kim; Jong Seong Kang; Byung Sun Min; Jong Keun Son; Mi Hee Woo (Natural Product Research, 2018)

Differential Expression under Podosphaera xanthii and Abiotic Stresses Reveals Candidate MLO Family Genes in Cucumis melo L - Jewel Howlader; Jong-In Park; Hoy-Taek Kim; Nasar Uddin Ahmed; Arif Hasan Khan Robin; Kanij Rukshana Sumi; Sathishkumar Natarajan; Ill-Sup Nou (Tropical Plant Biology, 2017)

Effects of spectral smearing of stimuli on the performance of auditory steady-state response-based brain–computer interface - Jong Ho Hwang; Kyoung Won Nam; Dong Pyo Jang; In Young Kim (Cognitive Neurodynamics, 2017)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Effects of vascular formation during alveolar bone process morphogenesis in mice - Seo-Young An; Ye-Ji Lee; Sanjiv Neupane; Jong-Hwa Jun; Ji-Youn Kim; Youngkyun Lee; Karp-Shik Choi; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Wern-Joo Sohn; Jae-Young Kim (Histochemistry and Cell Biology, 2017)

Genome-wide characterization and stress-responsive expression profiling of MCM genes in Brassica oleracea and Brassica rapa - Ashokraj Shanmugam; Arif Hasan Khan Robin; Senthil Kumar Thamilarasan; Harshavardhanan Vijayakumar; Sathishkumar Natarajan; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Journal of Plant Biology, 2017)

Ssanghwa-Tang, a traditional herbal formula, suppresses cigarette smoke-induced airway inflammation via inhibition of MMP-9 and Erk signaling - Je-Won Ko; Na-Rae Shin; Sung-Hyeuk Park; In-Chul Lee; Jung-Min Ryu; Young-Kwon Cho; Jong-Choon Kim; Chang-Seob Seo; In-Sik Shin (Molecular & Cellular Toxicology, 2017)

Discovery of candidate genes for heterosis breeding in Brassica oleracea L. - Seung-Yeon Jeong; Nasar Uddin Ahmed; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Acta Physiologiae Plantarum, 2017)

Plant growth promoting effect of Bacillus amyloliquefaciens H-2-5 on crop plants and influence on physiological changes in soybean under soil salinity - Min-Ji Kim; Ramalingam Radhakrishnan; Sang-Mo Kang; Young-Hyun You; Eun-Ju Jeong; Jong-Guk Kim; In-Jung Lee (Physiology and Molecular Biology of Plants, 2017)

Mechanism of protection by diallyl disulfide against cyclophosphamide-induced spermatotoxicity and oxidative stress in rats - Sung-Hwan Kim; In-Chul Lee; Je-Won Ko; In-Sik Shin; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Directing human embryonic stem cells towards functional endothelial cells easily and without purification - Chang-Hyun Gil; Byeong-Seong Ki; Joseph Seo; Jong-Jin Choi; Hana Kim; In-Gul Kim; A.-Ra Jung; Won-Young Lee; Youngsok Choi; Kwideok Park; Sung-Hwan Moon; Hyung-Min Chung (Tissue Engineering and Regenerative Medicine, 2016)

Protective effects of garlic oil against 1,3-dichloro-2-propanol-induced hepatotoxicity: role of CYP2E1 and MAPKs - Je-Won Ko; Sung-Hyeuk Park; In-Chul Lee; Sang-Min Lee; In-Sik Shin; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Bee Venom Acupuncture Alleviates Experimental Autoimmune Encephalomyelitis by Upregulating Regulatory T Cells and Suppressing Th1 and Th17 Responses - Min Jung Lee; Minhee Jang; Jonghee Choi; Gihyun Lee; Hyun Jung Min; Won-Seok Chung; Jong-In Kim; Youngheun Jee; Younbyoung Chae; Sung-Hoon Kim; Sung Joong Lee; Ik-Hyun Cho (Molecular Neurobiology, 2016)

Genome-Wide Classification and Abiotic Stress-Responsive Expression Profiling of Carotenoid Oxygenase Genes in Brassica rapa and Brassica oleracea - Yonguk Kim; Indeok Hwang; Hee-Jeong Jung; Jong-In Park; Jong-Goo Kang; Ill-Sup Nou (Journal of Plant Growth Regulation, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Role of Klotho, an antiaging protein, in pulmonary fibrosis - In-Sik Shin; Hyeun-Kyoo Shin; Jong-Choon Kim; Mee-Young Lee (Archives of Toxicology, 2015)

Microbial Additives in Controlling Odors from Stored Swine Slurry - Eunsun Choi; Jaehyuk Kim; Il Choi; Hyunmi Ahn; Jong In Dong; Hyunook Kim (Water, Air, & Soil Pollution, 2015)

Structural features of glycoprotein purified from Saccharina japonica and its effects on the selected probiotic properties of Lactobacillus plantarum in Caco-2 cell - Eun-Young Kim; S. M. Rafiquzzaman; Jong Min Lee; Gyuyou Noh; Geon-a Jo; Jong-Hee Lee; In-Soo Kong (Journal of Applied Phycology, 2015)

Application of distributed KIneMatic wave STOrm Runoff Model (KIMSTORM) for flood simulation considering dam release in the NamHan river basin of Korea - In-Kyun Jung; Dong-Ryul Lee; Jong-Yoon Park; Geun-Ae Park; Seong-Joon Kim (Paddy and Water Environment, 2015)

Expression of tobacco tocopherol cyclase in rice regulates antioxidative defense and drought tolerance - Hee-Jong Woo; Soo-In Sohn; Kong-Sik Shin; Jae-Kwang Kim; Beom-Gi Kim; Myung-Ho Lim (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Gordonibacter faecihominis sp. nov., isolated from human faeces - Jong-Sik Jin; Keun Chul Lee; In-Soon Park; Kwang Kyu Kim; Jong Seog Ahn; Yoshimi Benno; Masao Hattori; Jung-Sook Lee (Antonie van Leeuwenhoek, 2014)

Transcriptome analysis of mistletoe (Viscum album) haustorium development - Suk Min Ko; Yong Kook Kwon; Jong Hyun Kim; In-Ja Song; Hyo-Yeon Lee; Dong-Woog Choi; Jang R. Liu; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2014)

Serum Zinc Concentration Is Inversely Associated with Insulin Resistance but Not Related with Metabolic Syndrome in Nondiabetic Korean Adults - Bang-In Ahn; Moon Jong Kim; Hyung Suk Koo; Namkyung Seo; Nam-Seok Joo; Young-Sang Kim (Biological Trace Element Research, 2014)

Regulation of jasmonic acid biosynthesis by silicon application during physical injury to Oryza sativa L. - Yoon-Ha Kim; Abdul Latif Khan; Muhammad Waqas; Hee-Jeong Jeong; Duk-Hwan Kim; Jeong Sheop Shin; Jong-Guk Kim; Myung-Hun Yeon; In-Jung Lee (Journal of Plant Research, 2014)

Silver nanoparticles induce apoptotic cell death in cultured cerebral cortical neurons - Sung-Hwan Kim; Je-Won Ko; Suk-Kyu Koh; In-Chul Lee; Jung-Mo Son; Changjong Moon; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2014)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

Expression of a functional recombinant chimeric protein of human hepatitis A virus VP1 and an Fc antibody fragment in transgenic tomato plants - Ho Yong Chung; Jong-Hwa Park; Hyun Ho Lee; Kyung Il Kim; Ha Young Chung; Garry Sunter; Jong Bum Kim; Wonyong Kim; In Sik Chung (Plant Biotechnology Reports, 2014)

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Transcriptional activation of p21WAF1/CIP1 is mediated by increased DNA binding activity and increased interaction between p53 and Sp1 via phosphorylation during replicative senescence of human embryonic fibroblasts - Hyun-Seok Kim; Jee-In Heo; Seong-Hoon Park; Jong-Yeon Shin; Hong-Jun Kang; Min-Ju Kim; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Molecular Biology Reports, 2014)

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Additive or Synergistic Effects of Aluminum on the Reduction of Neural Stem Cells, Cell Proliferation, and Neuroblast Differentiation in the Dentate Gyrus of High-Fat Diet-Fed Mice - Sung Min Nam; Jong Whi Kim; Dae Young Yoo; Woosuk Kim; Hyo Young Jung; In Koo Hwang; Je Kyung Seong; Yeo Sung Yoon (Biological Trace Element Research, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Metabolic versatility of toluene‐degrading, iron‐reducing bacteria in tidal flat sediment, characterized by stable isotope probing‐based metagenomic analysis - So‐Jeong Kim; Soo‐Je Park; In‐Tae Cha; Deullae Min; Jin‐Seog Kim; Won‐Hyung Chung; Jong‐Chan Chae; Che Ok Jeon; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary DNA stable isotope probing and metagenomic sequencing were used to assess the metabolic potential of iron‐reducing bacteria involved in anaerobic aromatic hydrocarbon degradation in oil spill‐affected tidal flats. In a microcosm experiment, 13 C‐toluene was degraded with the simultaneous reduction of F e( III )‐ NTA , which was also verified by quasi‐stoichiometric 13 C‐CO 2 release. The metabolic potential of the dominant member affiliated with the genus Desulfuromonas in the heavy DNA fraction was inferred using assembled scaffolds (designated TF genome, 4.40 Mbp with 58.8 GC mol%), which were obtained by Illumina sequencing. The gene clusters with peripheral pathways for toluene and benzoate conversion possessed the features of strict and facultative anaerobes. In addition to the class II ‐type benzoyl‐ CoA reductase ( B am) of strict anaerobes, the class I ‐type ( B cr) of facultative anaerobes was encoded. Genes related to the utilization of various anaerobic electron acceptors, including iron, nitrate (to ammonia), sulfur and fumarate, were identified. Furthermore, genes encoding terminal oxidases ( caa 3 , cbb 3 and bd ) and a diverse array of genes for oxidative stress responses were detected in the TF genome. This metabolic versatility may be an adaptation to the fluctuating availability of electron acceptors and donors in tidal flats.

Dietary aflatoxin B1 intake, genetic polymorphisms of CYP1A2, CYP2E1, EPHX1, GSTM1, and GSTT1, and gastric cancer risk in Korean - Sang-Yong Eom; Dong-Hyuk Yim; Yanwei Zhang; Jung-Kuk Yun; Sun In Moon; Hyo-Yung Yun; Young-Jin Song; Sei-Jin Youn; Taisun Hyun; Joo-Seung Park; Byung Sik Kim; Jong-Young Lee; et al. (Cancer Causes & Control, 2013)

3-O-Acetyloleanolic acid exhibits anti-angiogenic effects and induces apoptosis in human umbilical vein endothelial cells - En-Ji Cui; Jeon Hwang-Bo; Jong-Hwa Park; Nam-In Baek; Jiyoung Kim; Seong Gil Hong; In Sik Chung (Biotechnology Letters, 2013)

Whole-genome sequence analysis of a Korean G11P[25] rotavirus strain identifies several porcine-human reassortant events - Van Thai Than; Jong-Hwa Park; In Sik Chung; Jong Bum Kim; Wonyong Kim (Archives of Virology, 2013)

Natronomonas gomsonensis sp. nov., isolated from a solar saltern - Tae-Yoon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Man-Young Jung; Sang-A Lee; Seong Woon Roh; Kyung June Yim; Takashi Itoh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Perverted Head Impulse Test in Cerebellar Ataxia - Seong-Hae Jeong; Ji-Soo Kim; In Chul Baek; Jong Wook Shin; Hyunjin Jo; Ae Young Lee; Jae-Moon Kim (The Cerebellum, 2013)

N-terminal region of rice polycomb group protein OsEZ1 is required for OsEZ1–OsFIE2 protein interaction - Jong-Kuk Na; Mi-Hye Seo; Seok-Jun Moon; In-Sun Yoon; Yeon-Hee Lee; Jae Kwang Kim; Kyun Oh Lee; Dool-Yi Kim (Plant Biotechnology Reports, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Melatonin improves adriamycin-induced hepatic oxidative damage in rats - In-Chul Lee; Sung-Hwan Kim; Hyung-Seon Baek; Changjong Moon; Chun-Sik Bae; Sung-Ho Kim; Won-Kee Yun; Ki-Hoan Nam; Hyoung-Chin Kim; Jong-Choon Kim (Molecular & Cellular Toxicology, 2013)

Miocene Tilia (Malvaceae) woods in Korea: including a new taxon - Eun Kyoung Jeong; Kyungsik Kim; In Sung Paik; Jong-Deock Lim (Geosciences Journal, 2013)

Influence of Sediment Grain Size and Land Use on the Distributions of Heavy Metals in Sediments of the Han River Basin in Korea and the Assessment of Anthropogenic Pollution - Tien M. Lai; Wonkyo Lee; Jin Hur; Younghun Kim; In-Ae Huh; Hyun-Sang Shin; Chan-Kook Kim; Jong-Hyun Lee (Water, Air, & Soil Pollution, 2013)

Neural substrates of acupuncture in the modulation of cravings induced by smoking-related visual cues: an FMRI study - O-Seok Kang; Song-Yi Kim; Geon-Ho Jahng; Hackjin Kim; Jong-Woo Kim; Sun-Yong Chung; Jun-Won Kim; Seung-In Yang; Hi-Joon Park; Hyejung Lee; Younbyoung Chae (Psychopharmacology, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

Hoeflea halophila sp. nov., a novel bacterium isolated from marine sediment of the East Sea, Korea - Man-Young Jung; Kee-Sun Shin; Suyeon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Mi-Na Kim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Effect of the size and surface charge of silica nanoparticles on cutaneous toxicity - Yoon-Hee Park; Hyun Cheol Bae; Yeonsue Jang; Sang Hoon Jeong; Ha Na Lee; Woo-In Ryu; Min Gun Yoo; Yu-Ri Kim; Meyoung-Kon Kim; Jong Kwon Lee; Jayoung Jeong; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Detection of Vibrio cholerae and Vibrio vulnificus by duplex PCR specific to the groEL gene - Muhammad Tofazzal Hossain; Yu-Ri Kim; Eun-Young Kim; Jong-Min Lee; In-Soo Kong (Fisheries Science, 2013)

Sequence polymorphisms in ribosomal RNA genes and variations in chromosomal loci of Oenothera odorata and O. laciniata - Jun Hyung Seo; Hyo Geun Bae; Da Hee Park; Beom Seok Kim; Jong Wook Lee; Jung In Lee; Dong Hyun Kim; Seok Won Lee; Bong Bo Seo (Genes & Genomics, 2013)

Effect of proton beam irradiation on germination, seedling growth, and pasting properties of starch in rice - Sang-Kuk Kim; Shin-Young Park; Kye-Ryung Kim; Jong-Hee Shin; Su-Yong Kim; Hak-Yoon Kim; In-Jung Lee (Journal of Crop Science and Biotechnology, 2012)

Gene expression profiles of human lung epithelial cells exposed to toluene - Yu-Ri Kim; In-Kyoung Kim; Seung Ho Lee; Eun-Jung Lee; Mi Jung Pyo; Hee Ra Lee; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Toxicology and Environmental Health Sciences, 2012)

Involvement of rice Polycomb protein OsFIE2 in plant growth and seed size - Jong-Kuk Na; Mi-Hye Seo; In-Sun Yoon; Yeon-Hee Lee; Kyun Oh Lee; Dool-Yi Kim (Plant Biotechnology Reports, 2012)

Melatonin attenuates gentamicin-induced nephrotoxicity and oxidative stress in rats - In-Chul Lee; Sung-Hwan Kim; Sang-Min Lee; Hyung-Seon Baek; Changjong Moon; Sung-Ho Kim; Seung-Chun Park; Hyoung-Chin Kim; Jong-Choon Kim (Archives of Toxicology, 2012)

Pycnogenol® prevents hexavalent chromium-induced spermatotoxicity in rats - Sung-Hwan Kim; In-Chul Lee; Hyung-Seon Baek; Changjong Moon; Seong-Soo Kang; Chun-Sik Bae; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Enhanced expression of recombinant human cyclooxygenase 1 from stably-transfected Drosophila melanogaster S2 cells by dimethyl sulfoxide is mediated by up-regulation of nitric oxide synthase and transcription factor Kr-h1 - Kyung Hwa Chang; Jong-Hwa Park; Ha Young Chung; Jeon Hwang-Bo; Hyun Ho Lee; Do Hyung Kim; Yunjo Soh; In Sik Chung (Biotechnology Letters, 2012)

Serum Selenium Levels in Korean Hepatoma Patients - In-Wook Kim; Su-Mi Bae; Yong-Wan Kim; Hai-Bo Liu; Si Hyun Bae; Jong Young Choi; Seung Kew Yoon; Pankaj Kumar Chaturvedi; Gantumur Battogtokh; Woong Shick Ahn (Biological Trace Element Research, 2012)

Expression of a recombinant chimeric protein of human colorectal cancer antigen GA733-2 and Fc fragment of antibody using a replicating vector based on Beet curly top virus in infiltrated Nicotiana benthamiana leaves - Kyung Il Kim; Ha Young Chung; Ki Hyun Yoo; Jong-Hwa Park; Hyun Ho Lee; Yeon Ju Soek; Ki Sung Ko; Hyung Sik Kang; Kyung Jin Lee; Doo-Byoung Oh; Young Hee Joung; In Sik Chung (Plant Biotechnology Reports, 2012)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Evaluation of soybean cultivars for resistance to phomopsis seed decay in Korea - Suli Sun; Kyujung Van; Moon Young Kim; Yeong-Ho Lee; Jong-Min Ko; In-Youl Baek; Yin-Won Lee; Weixian Liu; Suk-Ha Lee (Journal of Crop Science and Biotechnology, 2012)

El-Nino Southern Oscillation simulated and predicted in SNU coupled GCMs - Yoo-Geun Ham; In-Sik Kang; Daehyun Kim; Jong-Seong Kug (Climate Dynamics, 2012)

Pure culture of Metarhizium anisopliae LHL07 reprograms soybean to higher growth and mitigates salt stress - Abdul Latif Khan; Muhammad Hamayun; Sumera Afzal Khan; Sang-Mo Kang; Zabta Khan Shinwari; Muhammad Kamran; Shafiq ur Rehman; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2012)

Genomic characterization of a cell-culture-adapted Korean human G9P[8] rotavirus, CAU05-202 - Jong Wook Shin; Van Phan Le; Van Thai Than; Inseok Lim; Yoosik Yoon; Kijeong Kim; Sang-In Chung; Soon Chul Myung; Wonyong Kim (Archives of Virology, 2012)

Anti-inflammatory effects of kaempferol-3-O-sophoroside in human endothelial cells - Tae Hoon Kim; Sae-Kwang Ku; In-Chul Lee; Jong-Sup Bae (Inflammation Research, 2012)

5-Phenylselenyl- and 5-methylselenyl-methyl-2′-deoxyuridine induce oxidative stress, DNA damage, and caspase-2-dependent apoptosis in cancer cells - Byeong Mo Kim; Ambadas B. Rode; Eun Jong Han; In Seok Hong; Sung Hee Hong (Apoptosis, 2012)

Mutualistic association of Paecilomyces formosus LHL10 offers thermotolerance to Cucumis sativus - Abdul Latif Khan; Muhammad Hamayun; Ramalingam Radhakrishnan; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Jae-Ho Shin; Yeon-Sik Choo; Jong-Guk Kim; In-Jung Lee (Antonie van Leeuwenhoek, 2012)

Hepatoprotection of different water extracts from Acer tegmentosum M. on CCl4-induced acute hepatotoxicity in mice: comparative efficacies between the extracts of boughs, twigs, and leaves - Kwang-Yong Shim; Dong-Heui Kim; Soon-Bong Song; Xu-Feng Qi; Yang-Suk Yoon; Hyun-Soo Kim; Jong-In Lee; Hwa-Eun Oh; Soo-Ki Kim; Kyu-Jae Lee (Molecular & Cellular Toxicology, 2011)

A grid-based rainfall-runoff model for flood simulation including paddy fields - In-Kyun Jung; Jong-Yoon Park; Geun-Ae Park; Mi-Seon Lee; Seong-Joon Kim (Paddy and Water Environment, 2011)

Expression of a recombinant chimeric protein of hepatitis A virus VP1-Fc using a replicating vector based on Beet curly top virus in tobacco leaves and its immunogenicity in mice - Ho Yong Chung; Hyun Ho Lee; Kyung Il Kim; Ha Young Chung; Jeon Hwang-Bo; Jong Hwa Park; Garry Sunter; Jong Bum Kim; Dong Hwa Shon; Wonyong Kim; In Sik Chung (Plant Cell Reports, 2011)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

Isolation and characterization of 28 polymorphic SSR loci from castor bean (Ricinus communis L.) - Kyoung-In Seo; Gi-An Lee; Kyung-Ho Ma; Do-Yoon Hyun; Yong-Jin Park; Jong-Wook Jung; Sok-Young Lee; Jae-Gyun Gwag; Chung-Kon Kim; Myung-Chul Lee (Journal of Crop Science and Biotechnology, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

A new cloning strategy for generating multiple repeats of a repetitive polypeptide based on non-template PCR - Hun-Su Chu; Jung Ryum; Seo-Young Park; Byung-Gee Kim; Dong-Myung Kim; Jong-In Won (Biotechnology Letters, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Suppression of NH3 and N2O emissions by massive urea intercalation in montmorillonite - Kwang Seop Kim; Man Park; Choong Lyeal Choi; Dong Hoon Lee; Young Jin Seo; Chan Yong Kim; Jong Su Kim; Seok-In Yun; Hee-Myong Ro; Sridhar Komarneni (Journal of Soils and Sediments, 2011)

Extract of Poncirus trifoliata fruit reduces elevated serum IgE concentrations in chemically induced allergic model mice - Hyun Jung Park; Jong Bo Kim; In Song Han; Jin Hoi Kim; Bokyung Kim; Sung-Ho Kang; Ho-Sung Jung; Sang Ho Moon; Si Heung Sung; Hyuk Song (Horticulture, Environment, and Biotechnology, 2011)

Molecular characterization of rare G12P[6] rotavirus isolates closely related to G12 strains from the United States, CAU 195 and CAU 214 - Van Phan Le; Jong Bum Kim; Dong Hwa Shon; In Sik Chung; Yoosik Yoon; Kijeong Kim; Sang-In Chung; Inseok Lim; Wonyong Kim (Archives of Virology, 2011)

Synthesis of double-layered rotavirus-like particles using internal ribosome entry site vector system in stably-transformed Drosophila melanogaster - Jong Min Lee; Ha Young Chung; Kyung Il Kim; Ki Hyun Yoo; Jeon Hwang-Bo; In Sik Chung; Jong-Hwa Park (Biotechnology Letters, 2011)

Transformation of carotenoid biosynthetic genes using a micro-cross section method in kiwifruit (Actinidia deliciosa cv. Hayward) - Misun Kim; Seong-Cheol Kim; Kwan Jeong Song; Ho Bang Kim; In-Jung Kim; Eun-Young Song; Seung-Jong Chun (Plant Cell Reports, 2010)

Correlation between nutrition intake and gene expression profiles in children with asthma - Jae-Eun Pie; Yu-Ri Kim; In-Kyoung Kim; Sang-Hui Seo; Seung Ho Lee; Hee Ra Lee; Young Yoo; Ji Tae Chung; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Molecular & Cellular Toxicology, 2010)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)

Detection of replicating negative-sense RNAs in CaCo-2 cells infected with human astrovirus - So Young Jang; Weon Hwa Jeong; Mi Suk Kim; Young Min Lee; Jae In Lee; Gyu Cheol Lee; Soon Young Paik; Gwang Pyo Koh; Jong Min Kim; Chan Hee Lee (Archives of Virology, 2010)

Induction of Oxidative Stress in the Epididymis of Rats After Subchronic Exposure to Epichlorohydrin - In-Sik Shin; Jeong-Hyeon Lim; Sung-Hwan Kim; Kang-Hyeon Kim; Na-Hyeong Park; Chun-Sik Bae; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Woojin Jun; Jong-Choon Kim (Bulletin of Environmental Contamination and Toxicology, 2010)

Arabidopsis thaliana Rubisco small subunit transit peptide increases the accumulation of Thermotoga maritima endoglucanase Cel5A in chloroplasts of transgenic tobacco plants - Suyeon Kim; Dae-Seok Lee; In Seong Choi; Sung-Ju Ahn; Yong-Hwan Kim; Hyeun-Jong Bae (Transgenic Research, 2010)

Miocene woods of the Janggi Basin in Korea: Implications for paleofloral changes - Jong-Deock Lim; Eun-Kyoung Jeong; Kyungsik Kim; Mitsuo Suzuki; In Sung Paik; Haang-Mook Kim (Geosciences Journal, 2010)

Effects of the low-frequency zonal wind variation on the high frequency atmospheric variability over the tropics - K. P. Sooraj; Daehyun Kim; Jong-Seong Kug; Sang-Wook Yeh; Fei-Fei Jin; In-Sik Kang (Climate Dynamics, 2009)

A novel mutation in Hr causes abnormal hair follicle morphogenesis in hairpoor mouse, an animal model for Marie Unna Hereditary Hypotrichosis - In Cheol Baek; Jeong Ki Kim; Kyu-Hyuk Cho; Dal-Sun Cha; Jae-Woo Cho; Jong Keun Park; Chang-Woo Song; Sungjoo Kim Yoon (Mammalian Genome, 2009)

Anti-inflammatory effects of talosin A via inhibition of NF-kappaB activation in lipopolysaccharide-stimulated RAW264.7 cells - Youn-Hwan Hwang; Myoung-Seok Kim; In-Bae Song; Jong-Hwan Lim; Byung-Kwon Park; Hyo-In Yun (Biotechnology Letters, 2009)

Gibberellin production and plant growth promotion by a newly isolated strain of Gliomastix murorum - Sumera Afzal Khan; Muhammad Hamayun; Ho-Youn Kim; Hyeok-Jun Yoon; In-Jung Lee; Jong-Guk Kim (World Journal of Microbiology and Biotechnology, 2009)

Cladosporium sphaerospermum as a new plant growth-promoting endophyte from the roots of Glycine max (L.) Merr. - Muhammad Hamayun; Sumera Afzal Khan; Nadeem Ahmad; Dong-Sheng Tang; Sang-Mo Kang; Chae-In Na; Eun-Young Sohn; Young-Hyun Hwang; Dong-Hyun Shin; Byung-Hyun Lee; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Simulation of state-dependent high-frequency atmospheric variability associated with ENSO - Jong-Seong Kug; K. P. Sooraj; Daehyun Kim; In-Sik Kang; Fei-Fei Jin; Yukari N. Takayabu; Masahide Kimoto (Climate Dynamics, 2009)

A new strain of Arthrinium phaeospermum isolated from Carex kobomugi Ohwi is capable of gibberellin production - Sumera Afzal Khan; Muhammad Hamayun; Ho-youn Kim; Hyeok-jun Yoon; Jong-cheol Seo; Yeon-sik Choo; In-jung Lee; Sang-dal Kim; In-koo Rhee; Jong-guk Kim (Biotechnology Letters, 2009)

Variation in the phenotypic features and transcripts of color mutants of chrysanthemum (Dendranthema grandiflorum) derived from gamma ray mutagenesis - Geung-Joo Lee; Sung Jin Chung; In Sook Park; Jong Suk Lee; Jin-Baek Kim; Dong Sub Kim; Si-Yong Kang (Journal of Plant Biology, 2008)

Tropical Pacific impacts of convective momentum transport in the SNU coupled GCM - Daehyun Kim; Jong-Seong Kug; In-Sik Kang; Fei-Fei Jin; Andrew T. Wittenberg (Climate Dynamics, 2008)

The spatio-temporal expression pattern of cytoplasmic Cu/Zn superoxide dismutase (SOD1) mRNA during mouse embryogenesis - Jung-Min Yon; In-Jeoung Baek; Se-Ra Lee; Yan Jin; Mi-Ra Kim; Sang-Seop Nahm; Jong-Soo Kim; Byeongwoo Ahn; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2008)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

The Macroalgal Community of Bagryoungdo Island in Korea - Jae-Min Baek; Mi-Sook Hwang; Jae-Wan Lee; Wook-Jae Lee; Jong-In Kim (Algae, 2007)

Antiangiogenic and Apoptotic Properties of a Novel Amphiphilic Folate-Heparin-Lithocholate Derivative Having Cellular Internality for Cancer Therapy - Mi Kyung Yu; Dong Yun Lee; Yoo Shin Kim; Kyeongsoon Park; Soo Ah Park; Dai Hyun Son; Gee Young Lee; Jong Hee Nam; Sang Yoon Kim; In San Kim; Rang Woon Park; Youngro Byun (Pharmaceutical Research, 2007)

Hypoxia-induced cell death of HepG2 cells involves a necrotic cell death mediated by calpain - Min-Ju Kim; Soo-Jin Oh; Seong-Hoon Park; Hong-Jun Kang; Moo-Ho Won; Tae-Cheon Kang; In Koo Hwang; Jae-Bong Park; Jong-Il Kim; Jaebong Kim; Jae-Yong Lee (Apoptosis, 2007)

Identification of differentially expressed genes involved in spine formation on seeds ofDaucus carota L. (carrot), using annealing control primer (ACP) system - Jong-Sug Park; In Sun Kim; Moon Soo Cho; Shin Park; Sang Gyu Park (Journal of Plant Biology, 2006)

EFFECTS OF ULMUS DAVIDIANA PLANCH ON MINERALIZATION, BONE MORPHOGENETIC PROTEIN-2, ALKALINE PHOSPHATASE, TYPE I COLLAGEN, AND COLLAGENASE-1 IN BONE CELLS - SUNG-KOO KANG; KAP-SUNG KIM; YU-SEOK BYUN; SEOK-JONG SUH; UN-HO JIM; KYUNG-HO KIM; IN-SEON LEE; CHEORL-HO KIM (In Vitro Cellular & Developmental Biology - Animal, 2006)

Genetic analysis of phosphomannomutase/phosphoglucomutase from Vibrio furnissii and characterization of its role in virulence - Sun-Hoi Kim; Sun-Hee Ahn; Jong-Hee Lee; Eun-Mi Lee; Nam-Hyun Kim; Kee-Jai Park; In-Soo Kong (Archives of Microbiology, 2003)

Modified Magnetic Resonance Image Based Parcellation Method for Cerebral Cortex using Successive Fuzzy Clustering and Boundary Detection - Uicheul Yoon; Jong-Min Lee; Jae-Jin Kim; Sang Min Lee; In Young Kim; Jun Soo Kwon; Sun I. Kim (Annals of Biomedical Engineering, 2003)

Phylogenetic Relationship of Microcystis (Cyanophyceae) Based on Partial 16S rRNA Gene Sequences in Korea - Jong-In Kim; Jong-Hun Lim; Jae-Wan Lee; Hae-Bok Lee (Algae, 2002)

Dimethylsulfoxide and sodium butyrate enhance the production of recombinant cyclooxygenase 2 in stably transformed Drosophila melanogaster S2 cells - Kyung Hwa Chang; Jong Hwa Park; Youn Hyung Lee; Jong Ho Kim; Hyung Ok Chun; Je Hak Kim; In Sik Chung (Biotechnology Letters, 2002)

Curdlan gels as protein drug delivery vehicles - Beom Soo Kim; In Duck Jung; Jong Sik Kim; Jung-heon Lee; In Young Lee; Kyung Bok Lee (Biotechnology Letters, 2000)

Embryo lethality and teratogenicity of a new fluoroquinolone antibacterial DW-116 in rats - Jong-Choon Kim; Hyo-In Yun; Ho-Chul Shin; Sang-Seop Han; Moon-Koo Chung (Archives of Toxicology, 2000)

Production of recombinant rotavirus VP6 from a suspension culture of transgenic tomato (Lycopersicon esculentum Mill.) cells - In Sik Chung; Chang Heon Kim; Kyung Il Kim; Seong Hyun Hong; Jong Hwa Park; Ju Kon Kim; Won Yong Kim (Biotechnology Letters, 2000)

Analysis of somaclonal variation through tissue culture and chromosomal localization of rDNA sites by fluorescent in situ hybridization in wild Allium tuberosum and a regenerated variant - Geum-Sook Do; Bong-Bo Seo; Jong-Min Ko; Seon-Hee Lee; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Characterization of a mouse monoclonal IgG3 antibody to the tumor-associated globo H structure produced by immunization with a synthetic glycoconjugate - Valery Kudryashov; Govindaswami Ragupathi; In Jong Kim; Michael E Breimer; Samuel J Danishefsky; Philip O Livingston; Kenneth O Lloyd (Glycoconjugate Journal, 1998)

Decrease in carbamylation of rubisco by high CO2 concentration is due to decrease of rubisco activase in kidney bean - Kwang Soo Roh; In Seob Kim; Byung Weon Kim; Jong Suk Song; Hwa Sook Chung; Seung Dal Song (Journal of Plant Biology, 1997)